The Use of Coding in a Situational Analysis of the Political Participation of Indigenous People in Chile's Constitutional Process - Héctor Turra Chico (Forum: Qualitative Social Research)
In situational analysis (SA), various procedures are available, including coding and mapping, each serving distinct purposes at different levels of the research process. In this article, I present a case regarding the uses of coding based on a research project focused on the political participation of Indigenous peoples in Chile's constitutional process. The motivation for this article stems from the challenges I encountered as a newcomer to SA.